2023
DOI: 10.3847/1538-4357/aca527
|View full text |Cite
|
Sign up to set email alerts
|

Kilonovae and Optical Afterglows from Binary Neutron Star Mergers. II. Optimal Search Strategy for Serendipitous Observations and Target-of-opportunity Observations of Gravitational Wave Triggers

Abstract: In the second work of this series, we explore the optimal search strategy for serendipitous and gravitational-wave-triggered target-of-opportunity (ToO) observations of kilonovae and optical short-duration gamma-ray burst (sGRB) afterglows from binary neutron star (BNS) mergers, assuming that cosmological kilonovae are AT2017gfo-like (but with viewing-angle dependence) and that the properties of afterglows are consistent with those of cosmological sGRB afterglows. A one-day cadence serendipitous search strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 185 publications
(183 reference statements)
2
4
0
Order By: Relevance
“…We find that under the dark night-sky background of the site in Table 1, the detection depths considering image subtraction are shallower than those calculated by comparing the kilonova magnitude with the limiting magnitude of the telescope. Given the spectrum of an AT2017gfo-like kilonova, the g and r bands are more effective in searching for kilonovae, which is consistent with the results in Zhu et al (2023) and Chase et al (2022). If the kilonova is not detected around peak, the longer-wavelength bands can be useful to keep searching according to the spectral evolution of kilonovae (Kasen et al 2017).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We find that under the dark night-sky background of the site in Table 1, the detection depths considering image subtraction are shallower than those calculated by comparing the kilonova magnitude with the limiting magnitude of the telescope. Given the spectrum of an AT2017gfo-like kilonova, the g and r bands are more effective in searching for kilonovae, which is consistent with the results in Zhu et al (2023) and Chase et al (2022). If the kilonova is not detected around peak, the longer-wavelength bands can be useful to keep searching according to the spectral evolution of kilonovae (Kasen et al 2017).…”
Section: Discussionsupporting
confidence: 73%
“…Recently, some studies on kilonova detectability predicted the expected number of kilonovae for various wide-field instruments Their research concluded that it is more effective to search for kilonovae after a GW trigger than via serendipitous observations. By considering the afterglows of sGRBs and the viewing angle, for AT2017gfo-like kilonovae, Zhu et al (2023) studied the prospect of finding different combinations of kilonovae and GRB afterglows. Chase et al (2022) calculated the detection depth of thirteen wide-field instruments based on a specific kilonova model and a grid of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…A magnitude of 24.7 is bolded to represent the r-band limiting magnitude for LSST and these calculations assume that D lim,KN ∼ 90 Mpc for BNS mergers and ∼ 175 Mpc for BHNS mergers. The BNS and BHNS kilonova event rates are similar to those predicted in Zhu et al (2023) and Gupta et al (2023), respectively, where similar volumetric rate, EOS, and LSST observation assumptions are made (and both include more in depth studies on the prospects for GW detection as a trigger for target-of-opportunity multimessenger searches).…”
Section: ; Abbott Et Al 2017bsupporting
confidence: 53%
“…This makes BHNS kilonovae an intriguing source with different cadence requirements compared to BNS kilonovae. Whereas BNS kilonovae require a cadence of 1 − 2 days (Zhu et al 2022(Zhu et al , 2023, BHNS kilonovae should require a cadence of 1 − 3 days for multiple observing epochs (Zhu et al 2021b).…”
Section: ; Abbott Et Al 2017bmentioning
confidence: 99%
“…It should be noted that combining these detection channels with targets of opportunity from GRB detectors, is expected to increase even further the number of events. Also, as the detection rate is ∝D 3 , future third-generation GW detectors (Cosmic Explorer, Reitze et al 2019;Einstein Telescope, Punturo et al 2010a, 2010bMaggiore et al 2020) expected in the coming decade and with future wide field detectors (e.g., LSST; Ivezić et al 2019) will dramatically increase the detection rate by ∼3 orders of magnitude (e.g., Zhu et al 2023).…”
Section: Detection As An Em Counterpart To Gwmentioning
confidence: 99%